Construction of the 5,10b-phenanthridine skeleton using [3+2]-cycloaddition of a non-stabilized azomethine ylide: total synthesis of (+/-)-maritidine and (+/-)-crinine alkaloids - Pandey, Ganesh; Gupta, Nishant R.; Gadre, Smita R. (European Journal of Organic Chemistry, 2011)
Vicinal quaternary and tertiary stereocenters of the 5,10b-phenanthridine skeleton 1 are constructed simultaneously in one step by the [3+2]-cycloaddition of non-stabilized azomethine ylide 9, generated by sequential double desilylation of 10 utilizing silver(I) fluoride as a one-electron oxidant. The regioas well as stereochemical origin of this cycloaddition reaction is explained through a favorable transition state 9''. The strategy is successfully applied for the total synthesis of the biologically active alkaloids (+/-)-maritidine (1a), (+/-)-crinine (1b), and their analogues (1d, 1e, and 1f).
Keywords: alkaloids; Azomethine ylides; Cycloaddition; Natural products; Ylides

One-step stereospecific strategy for the construction of the core structure of the 5,11-methanomorphanthridine alkaloids in racemic as well as in optically pure form: synthesis of (+/-)-pancracine and (+/-)-brunsvigine - Pandey, Ganesh; Kumar, Ravindra; Banerjee, Prabal; Puranik, Vedavati G. (European Journal of Organic Chemistry, 2011)
The unique core structure of the complex pentacyclic 5,11-methanomorphanthridine has been constructed stereospecifically in one step by an intramolecular [3+2] cycloaddition of a non-stabilized azomethine ylide (AMY), generated by the sequential double desilylation of 14 using (AgF)-F-I as a one-electron oxidant. The formation of the single diastereomer in the key step is explained by the preferred transition state produced by endo attack of the AMY on the ``Re'' face of the dipolarophile. An asymmetric version of the cycloaddition using a chiral dipolarophile was applied to construct the core structure 68 with 63 % ee. This strategy was successfully applied to the formal synthesis of (+/-)-pancracine and the total synthesis of (+/-)-brunsvigine. An unprecedented and interesting skeletal rearrangement product 49 was observed during the attempted assembly of the E ring from 46 through Horner-Wadsworth-Emmons reactions. Mechanisms involving azetidinium salt formation or the Grob-type fragmentation are advanced to explain the observed rearrangement.
Keywords: alkaloids; Azomethine ylides; Cycloaddition; Ring-closing metathesis; synthesis design